DAYA HIDUP DAN INTENSITAS SERANGAN RAYAP KAYU KERING CRYPTOTERMES CYNOCEPHALUS LIGHT. PADA KAYU KELAPA (COCOS NUSIFERA L.) - Ginuk Sumarni (Jurnal Penelitian Hasil Hutan, 1988)
This  study   investigated   termite survival  and  infestation   intensity    on  coconut   wood.  For  this purpose dry  wood termite  Cryptotermes  cynocephalus Light. has been  used  in the  experiment.   Fifteen   worker  termites   were placed  in the wood  coconut  samples.  The size  of  each sample  is 1,5 cm  by 2,5 cm  by  5,0  cm. Samples  were taken  from  the periphery and  center  of  base of  stem,   the  periphery   and  center  of  middle  of  stem  and  the periphery   and center of  top  of  stem .The result revealed that  the highest dry wood  termite  survival accured  at the central part  of the top of stem  (37,3%), where  as the highest  infestation intensity accured  at  the  base of  the stem.